A theoretical study on dry reforming of methane (CDRM) over cobalt metal - Çimenoğlu, Vasfiye. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
The aim of this study is to analyze the adsorption and reaction steps of CDRM on the Co(111) surface by using DFT calculations. In this context, the adsorption/coadsorption of reactants, reaction intermediates, and the reaction were studied. LDOS analysis was also used whenever detailed analysis is necessary. In this study, adsorption behaviours of all reactants some products and intermediate products of CDRM reaction were investigated first. CO2 was adsorbed on all sites of Co(111) surface but adsorption energies and LDOS profiles show that the strengths of CO2 adsorption on those sites are very low. On the other hand, CH4 adsorption is either unstable or yields CH3 and H stabilized on the surface. CO adsorptions on all sites were found very strong with very similar adsorption energies. CH3 adsorption is stable on all sites, except on the bridge site, and the adsorption is strong. CH3 initially placed at bridge position assumed Hhcp position upon energy optimization. The most favorable sites for CH3 and CO adsorptions were Hhcp and atop sites, respectively. Simulation results show that oxygen adsorption is stable only at Hhcp site as O adsorbed on other sites assume Hhcp position upon energy optimization. In the second part of the work, 'C and O', and 'CO and CH3' coadsorption systems were studied for different surface concentration and adsorption configuration combinations. C and O coadsorption studies revealed that the energy optimized structures are very sensitive to relative surface coverages of the adsorbates as well as whether there is site competition between them; C and O interaction yield CO only when there is site competition. Finally, the TS searches of CH4 dehydrogenation and CO formation were carried out to obtain the reaction pathways and activation energies of elementary steps. CH4 dehydrogenation step was found as the rate-determining step of hydrogen and surface carbon production. Since CH dehydrogenation has high energy barrier and the strong endothermicity, CH dehydrogenation was found unfavorable both kinetically and thermodynamically. On the other hand, CO formation is an exothermic process and was found favorable.
Keywords: Metals -- Cobalt content.; Methane.